2014
DOI: 10.3389/fneur.2014.00126
|View full text |Cite
|
Sign up to set email alerts
|

Combining Non-Pharmacological Treatments with Pharmacotherapies for Neurological Disorders: A Unique Interface of the Brain, Drug–Device, and Intellectual Property

Abstract: Mobile medical applications (mHealth), music, and video games are being developed and tested for their ability to improve pharmacotherapy outcomes and medication adherence. Pleiotropic mechanism of music and gamification engages an intrinsic motivation and the brain reward system, supporting therapies in patients with neurological disorders, including neuropathic pain, depression, anxiety, or neurodegenerative disorders. Based on accumulating results from clinical trials, an innovative combination treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 87 publications
0
50
0
Order By: Relevance
“…To innovate treatments for neurological disorders, we have been studying diverse strategies to integrate digital health technologies with CNS drugs (4)(5)(6). Digital health is a branch of healthcare that employs internet, digital, and mobile technologies for improving health and/or treating diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To innovate treatments for neurological disorders, we have been studying diverse strategies to integrate digital health technologies with CNS drugs (4)(5)(6). Digital health is a branch of healthcare that employs internet, digital, and mobile technologies for improving health and/or treating diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Music showed clinical benefits of reducing acute and chronic pain (25)(26)(27). For epilepsy, there is clinical and preclinical evidence that specific musical compositions exert anticonvulsant effects (4,(28)(29)(30)(31)(32). Clinical studies showed that exposure to Mozart's K.448 sonata in pediatric epilepsy patients, even those with refractory seizures, caused a significant reduction of seizure frequency and epileptiform discharges (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progress in wireless and mobile EEG interfaces [198, 199] or the EDA-sensors offers unique opportunities for biofeedback-based streaming of digital content developed specifically for epilepsy patients [3]. Examples of online and mobile technologies and apps for epilepsy patients are studied and reviewed [195, 196, 200].…”
Section: Incentivized Therapiesmentioning
confidence: 99%
“…Therefore, an alternative method for the prevention and treatment of epilepsy is zurgently needed. Currently, nonpharmacological epilepsy treatments offer alternative treatment options [11,[22][23][24][25][26], of which music therapy has received increasing attention. Studies have suggested that specific auditory stimuli (such as Mozart K.448, i.e., Mozart's Sonata for Two Pianos in D Major, K.448 [27]) can be effective at reducing seizures and may even completely control seizures [28,29].…”
mentioning
confidence: 99%